Maintaining Ethnic Boundary: The Ethnogenesis of Madhesi Identity in Nepal Tarai (Patan Pragya, 2021)
This article attempts to illuminate on the processes wherein diverse groups of Madhesi people of the central Tarai have been ethnicized to form a shared identity in the specific historical and socio-political context of Nepal. Drawing on the perceptions and subjective experiences of Madhesi individuals in terms of their identity, it is argued that Madhesi identity has come into being and maintained through the practices of boundary maintenance that encompasses relational processes of inclusion and exclusion. Madhesi people have re(asserted) their cultural contrast to the Pahadis and claim political autonomy of the Tarai territory where they belong for making ethnic distinction and maintaining group boundary.